PROSES PENCIPTAAN KARYA TARI LAKU JANTRA - Riadiana Wita Januarika; Dwi Rahmani (TAMUMATRA, 2026)
This research examines the  Laku Jantra dance work, choreographed by Riadiana Wita Januarika in 2022, embodies the values of perseverance and determination in achieving aspirations. The spirit and resilience are symbolized through the character Arimbi. Presented as a group dance with a thematic narrative, Laku Jantra is structured into four acts: the introduction, depicting inner turmoil and desire; the first act, illustrating feminine grace; the second act, envisioning the fulfillment of aspirations; and the final act, portraying anger that transitions into acceptance and self-affirmation. This study employs a qualitative research method with a descriptive approach to analyze the creative process and structure of Laku Jantra. Alma M. Hawkins' theory, as outlined in Creating Through Dance, is used to explore the stages of creation, encompassing exploration, improvisation, and composition. Additionally, Maryono’s theory from Analisa Tari is utilized to examine the verbal and non-verbal components of the dance form. The findings reveal that the structure of Laku Jantra comprises verbal elements such as dialogue, monologue, and contemplative vocals, alongside non-verbal artistic components, including theme, storyline, movements, floor patterns, costumes, music, stage design, and lighting. The choreographic movements are rooted in the traditional Surakarta-style female dance vocabulary, further developed to align with the artistic vision. This research contributes valuable insights into the creative process and structural analysis of contemporary dance, serving as a comprehensive reference for scholarly exploration in the field.